Single-Dose Psilocybin for a Treatment-Resistant Episode of Major Depression - Goodwin, Guy M; Aaronson, Scott T; Alvarez, Oscar; Arden, Peter C; Baker, Annie; Bennett, James C; Bird, Catherine; Blom, Renske E; Brennan, Christine; Brusch, Donna; Burke, Lisa; Campbell-Coker, Kete; et al. (The New England journal of medicine, 2022)
BACKGROUND: Psilocybin is being studied for use in treatment-resistant depression. METHODS: In this phase 2 double-blind trial, we randomly assigned adults with treatment-resistant depression to receive a single dose of a proprietary, synthetic formulation of psilocybin at a dose of 25 mg, 10 mg, or 1 mg (control), along with psychological support. The primary end point was the change from baseline to week 3 in the total score on the Montgomery-Åsberg Depression Rating Scale (MADRS; range, 0 to 60, with higher scores indicating more severe depression). Secondary end points included response at week 3 (≥50% decrease from baseline in the MADRS total score), remission at week 3 (MADRS total score ≤10), and sustained response at 12 weeks (meeting response criteria at week 3 and all subsequent visits). RESULTS: A total of 79 participants were in the 25-mg group, 75 in the 10-mg group, and 79 in the 1-mg group. The mean MADRS total score at baseline was 32 or 33 in each group. Least-squares mean changes from baseline to week 3 in the score were -12.0 for 25 mg, -7.9 for 10 mg, and -5.4 for 1 mg; the difference between the 25-mg group and 1-mg group was -6.6 (95% confidence interval [CI], -10.2 to -2.9; P<0.001) and between the 10-mg group and 1-mg group was -2.5 (95% CI, -6.2 to 1.2; P = 0.18). In the 25-mg group, the incidences of response and remission at 3 weeks, but not sustained response at 12 weeks, were generally supportive of the primary results. Adverse events occurred in 179 of 233 participants (77%) and included headache, nausea, and dizziness. Suicidal ideation or behavior or self-injury occurred in all dose groups. CONCLUSIONS: In this phase 2 trial involving participants with treatment-resistant depression, psilocybin at a single dose of 25 mg, but not 10 mg, reduced depression scores significantly more than a 1-mg dose over a period of 3 weeks but was associated with adverse effects. Larger and longer trials, including comparison with existing treatments, are required to determine the efficacy and safety of psilocybin for this disorder. (Funded by COMPASS Pathfinder; EudraCT number, 2017-003288-36; ClinicalTrials.gov number, NCT03775200.).
Keywords: depresivní porucha unipolární; výsledek terapie; Depressive Disorder, Treatment-Resistant; dvojitá slepá metoda; deprese nereagující na léčbu; antidepresiva; Depressive Disorder, Major; Treatment Outcome; Adult; psilocybin; lidé; dospělí; Double-Blind Method; deprese; Antidepressive Agents; Depression; Humans; Psilocybin